Romantic Disillusionment and Environmental Catastrophe in Nigerian Petrocinema Film - Blood Vessel - Abdulhamid Badru,; Jamaluddin Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cinema, particularly petrocinema, has explored the socio-political and environmental consequences of oil extraction globally. The representation of oil and its socio-political impacts have not been sufficiently analysed, particularly within Nigerian cinema. The problem lies in the lack of critical analysis of how Nigerian films anthropomorphically depict petro-narratives, reflecting corporate influence and exposing the environmental and social injustices tied to oil exploitation. The study aims to investigate how Nigerian petrocinema functions as both a medium that conceals and challenges hegemonic power structures linked to oil extraction, with a particular focus on the intersection of oil, politics, and environmental degradation. Drawing on Ivakhiv's concept of anthropomorphism, this study textually analyses the postcolonial film Blood Vessel (Inwang, 2023) to uncover the environmental subjective ideological and symbolic meanings. Our findings reveal that Nigerian petrocinema critiques the marginalisation of local communities exposing the liminality space between tradition and modernity, highlighting the profound cultural and spiritual connections these populations maintain with their environment. The film exposes the environmental degradation caused by multinational corporations and government neglect, while emphasising community resilience and resistance. This finding demonstrates that Nigerian petrocinema uses anthropomorphism to humanise environmental issues, fostering a deeper understanding of the cultural and ecological impacts of oil exploitation. By challenging dominant narratives, the film advocate for environmental justice and the preservation of cultural identity and traditional ecological knowledge. This study contributes to broader discussions of petrocinema as a tool for cultural resistance and advocacy, providing insights into the complex interplay between petro, power, and identity in postcolonial societies.